INTERKONEKSITAS DALAM AJARAN SOSIAL TASAWUF SUNNI DAN FALSAFI - Khusnul Khotimah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2015)
The existence of Sunni and philosophical mysticism in the study of Sufism has its own epistemology. Discussing the polemic between Sunni and philosophical Sufism is risky because instead of the differences between them, there is prevalent interrelation between them. Therefore, interconnecting between the two models of Sufism deserves to be taken into a deeper study because Sufism may emerge as a moral movement towards social, political, moral, and economic inequalities committed by Muslims. The interconnectivity between Sunni and Falsafi Sufism were found in the spread of Islam around the archipelago. In this case, Islam first entered the archipelago by applying philosophical Sufism, such as pantheism in the Java community. Both Sunni and falsafi Sufism leads to personal moral perfectness self, by which the person can influence other people by his/her good behavior such as having self-control, obeying the parents, being wise and just, as well as regarding other people’s beliefs. The teaching of suni and falsafi Sufism has a significant role in social change and its follower’s spirituality, such as the spread of Islam around the archipelago, and the teaching for equality. Keberadaan tasawuf sunni dan falsafi dalam studi tasawuf memiliki epistemologi keilmuan tersendiri. Memperbincangkan polemik antara tasawuf sunni dan falsafi adalah hal yang riskan, karena masing-masing memiliki kecenderungan yang berbeda-beda, namun melakukan interkoneksi antara kedua model tasawuf tersebut menjadi kajian yang patut untuk ditelaah, karena tasawuf merupakan gerakan moral terhadap ketimpangan sosial, politik, moral dan ekonomi yang dilakukan umat Islam. Interkoneksitas tasawuf Sunni dan Falsafi tampak pada proses Islamisasi di Nusantara, di mana pertama Islam masuk ke Nusantara banyak menggunakan tasawuf falsafi, seperti paham panteisme dalam masyarakat Jawa. Tasawuf sunni dan falsafi bermuara pada kesempurnaan moral diri sendiri yang berdampak pada orang lain, dengan cara pengendalian hawa nafsu, menghormati kepada orang lain, bersikap bijaksana, adil serta menghormati  kepercayaan orang. Ajaran sosial tasawuf suni dan falsafi memiliki peran yang cukup besar dalam perubahan sosial masyarakat, antara lain tentang Islamisasi di Nusantara, dan ajaran kesetaraan, sehingga telah menempatkan tasawuf sunni dan falsafi memiliki peran yang cukup signifkan dalam pengamalan spiritual pengikutnya.